Discussion on Small Probability Correlation Analysis Technique of Security Audit System for Telecom Operator - Jian Guo; Jie Shen (Dianxin kexue)
The importance and difficulties of security audit software correlation analysis technique of business support system（BSS）for telecom operator was analyzed，and then solutions for small probability correlation analysis were proposed.Finally the model principle of small probability correlation analysis，design method，implementation steps and actual effects were described.